Analysis of Factors Related to the Implementation of the Policy of the Regent of Asahan Regency Regulation No. 71 of 2018 Concerning Smoke-Free Areas in Places of Worship in Aek Songsongan District - Lestari, Winda Sri; Gurning, Fitriani Pramita (Jurnal Kesmas Prima Indonesia, 2025)
According to the decision of the Asahan Regent Regulation Number 71 of 2018 concerning smoke-free areas, it has been decided that the existence of smoking rooms for active and passive people is a danger. This increase in prevalence can be seen in Indonesia, where around 500 people die every day from cigarettes. This study analyzed the elements of implementing the Asahan Regent Regulation No. 71 of 2018 concerning Smoke-Free Zones (KTR) in Houses of Worship in Aek Songsongan District. The type of research used is quantitative, using an analytical sampling research model with a sectional approach. The sampling technique is accidental sampling based on the study's results. The participants in this study were all mosque congregations and those who visited the mosque in Aek Songsongan District, with 96 respondents. Data collection used a questionnaire, and the variables studied included communication factors, resources, disposition/attitude, and bureaucratic structure. The data was processed using the Chi-Square test with the SPSS 21 application. According to the results of this study, there is a correlation between the Communication factor and policy implementation (p-value = 0.003) with an OR of 5.471, a relationship between the Resource factor (p-value = 0.002) with an OR of 0.123, a relationship between the Disposition/Attitude factor (p-value = 0.037) with an OR of 0.249, and a relationship between the Disposition/Attitude factor (p-value = 0.037) and an OR of 0.249.